PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Pada Perusahaan Sektor Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - LEIKHA AIDILA MAHSA PUTRI ; Satriya Candra Bondan Prabowo (Manajemen FEB - UB, 2018)
This study aims to determining the effect of ownerships, leverage, and firm size on the dividend policy. The independent variables are insider ownership, institusional ownership, leverage, and firm size. The dependent variable is dividend policy measured using dividend payout ratio. The population in this research is 144 manufacturing companies, all of them were selected as the sample through purposive sampling technique and get 12 manufacturing companies. The partial test of the research shows that insider ownership has significant relation with dividend policy, institusional ownership has significant relation with dividend policy, leverage has no significant relation to dividend policy (collateralizable assets has no significant relation to dividend policy and debt to total assets has no significant relation with dividend policy), and firm size has significant relation with dividend policy. Keywords: Dividend Policy, Insider Ownership, Institusional Ownership, Leverage and Firm Size.